Alterations in the kinetic activity of aromatlc-L-amino acid decarboxylase and preliminary 2-DE investigation of the brains in a 6-OHDA induced Parkinson's disease rat model - OGAN, AYŞE; ONAT, FİLİZ; GÜLHAN, REZZAN (My University, 2003)
Objective: The aim of this study was to isolate and purify the aromatic-L-amino acid decarboxylase (AADC,EC 4.1.1.28) enzyme rats from Parkinson\"s Disease (PD) induced and the healthy control group rat brains and compare the alterations in the kinetic activities of the isolated enzyme. The protein spots displaying on the 2-DE patterns of the diseased and the healthy control group crude rat brain homogenates were evaluated. Medhods: In this study, the Parkinson\"s Disease model was induced by injecting 6-hydroxydopamine into the brains of the rats. The PD model formation was successful in two rats out of three. Results: The AADC decarboxylase was isolated and partially purified by DEAE-Sephacel ion exchange chromatography from the brains of PD induced and healthy control animals to compare the kinetic activity of the enzyme. The kinetic activity of the enzyme was reduced 70% in the PD group compared to controls. In order to determine and correlate the alterations with PD, and the distribution of the proteins displayed by the crude brain homogenates of the diseased and the healthy control group both were investigated. Polyacrylamide gel electrophoresis (PAGE) of the crude brain homogenates under the native and denaturizing conditions displayed matching bands for both of the groups, while two dimensional electrophoresis (2-DE) patterns of the crude brain homogenates of the diseased and the control group displayed considerable differences. Conclusion: The results of this study confirm the power of 2-DE-PAGE technique of the proteome analysis. Currently only the proteome analysis enables the identification of disease correlated proteins.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; 2-DE; AADC; Parkinson Disease; Proteome; Proteome; Parkinson Disease; AADC; 2-DE